Education In Preparing Psychology Of Pregnant Mothers To Face Delivery The Covid-19 Puskesmas (Community Health Center) The Year 2022 - Agnes Bekti Wardani; Feva Tridiyawati (Lembaga Pengembangan Kinerja Dosen, 2022)
At the beginning of 2020, the world was shocked by the outbreak of a new virus, namely the coronavirus of type (SARS-CoV-2), and the disease is called Coronavirus disease 2019 (COVID-19). It is known, that the origin of this virus came from Wuhan, China, which was discovered at the end of December 2019. In this COVID-19 pandemic situation, the government made a policy of limiting almost all routine services, one example of which is maternal and neonatal health services and service facilities. other health. This causes anxiety in pregnant women so that they delay carrying out pregnancy tests. The type of this research is quantitative research, using the solving method in sample collection. While the testing in this study includes the validity test and reliability test. The findings of this study explain that the results of the reliability test also show that the data is declared reliable because of the value of Cronbach's Alpha > r table. The results showed that online media education was better than offline education in preparing the psychology of pregnant women to face childbirth in the COVID-19 era at Batuceper Health Center in 2022.